Problems of the Action of Euthanasia as Part of Human Rights - Febriansyah, Febriansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
One of the protections for human rights in the Constitution can be seen from the guarantee provided by Article 27 of the 1945 Constitution which states that "every citizen has the same position before the law and government with no exceptions". Euthanasia or death injections when viewed from the aspects of criminal law and human rights in Indonesia are still experiencing debates that have not found an end, because between the provision of human rights and the conflict of national laws, especially the Criminal Code imposed in Indonesia, but basically that the act of euthanasia is still an act that is prohibited in the criminal law system and health law in Indonesia.